A Follow-Up Report of an Infant Born to a Mother Receiving Tamoxifen - Yuki Okada; Daisuke Hitaka; Takahiro Kido; Yu Kanai; Kumi Konishi; Kosuke Doki; Nobuko Katayama; Masato Homma; Yayoi Miyazono; Hidetoshi Takada (Case Reports in Pediatrics)
Tamoxifen, an estrogen receptor antagonist, is contraindicated in pregnant women due to its teratogenic activity. In the present study, we report the case of an infant whose mother received tamoxifen for breast cancer while unaware of the pregnancy. The infant, born at 29 weeks and 6 days of gestational age with a birth weight of 1664 g, had no congenital anomalies. This case presents detailed information on the development of an infant with placental transfer of tamoxifen. The infant has grown and developed normally throughout a 5-year follow-up period, but long-term vigilance continues.